Socio-economic and cultural aspects associated with the cultivation of native cocoa in the original community U mukai, Bagua, Amazonas - López Cuadra, Yelka Martina (2020)
Peru ranks second worldwide as a producer and exporter of organic cocoa. The resource has significant social relevance as it is the sixth most important crop nationwide in terms of the number of residents engaged in the activity. In that sense, the objective of the research was to determine the socio-economic and cultural aspects associated with the cultivation of native cocoa in the original community Umukai, Imaza district, Bagua province, Amazonas region, 2019. The type of research is descriptive, quantitative and transectional; The data were obtained through systematic observation and through the application of a survey of cocoa producers in the community under study. The results obtained show that the Umukai cocoa producer is mostly male whose ages range from 30to 39 years; they present primary and secondary studies, which is limiting for the agricultura! technological adoption that allows the improvement of their production. Likewise, cocoa (Theobroma cacao L.) plays a very important economic role, because it guarantees its economic support. These comuneros use the Creole seed, without improvement, which implies a production of native cocoa. The climate, the biodiverse ecosystem and the native management will allow this natural variety, whose demand in the global markets is growing, to consolidate efficient nutrient management and adequate pruning to improve productivity. They leamed the cultivation of cocoa on their own and still use ancestral techniques such as minga or strength change; However, the use of wages in sowing and harvesting is increasingly growing. The socio-economic and cultural characteristics presented by the original Umukai community of Bagua, show that the cultivation of native cocoa represents a fundamental economic activity of the community, therefore, improvement, training or transformation plans on the resource should be promoted to ensure the sustainability ofthe same over time and the improvement ofthe quality oflife in the region.